HUBUNGAN PENGETAHUAN ERGONOMI TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA PT. PP PROYEK KONSTRUKSI BALI INTERNATIONAL HOSPITAL SANUR - Kirana, Padma Devi Indu; Sucipta Putri, Wayan Citra Wulan (ARCHIVE OF COMMUNITY HEALTH, 2025)
ABSTRACT Musculoskeletal Disorders (MSDs) are disorders or damage to muscles, joints, ligaments and other skeletal systems in the human body caused by inappropriate body positions, especially if done for a long time. Good ergonomic knowledge in workers can reduce the risk of injury. MSDs cases in 2018 amounted to 7.9% in Indonesia. The highest prevalence based on diagnosis is found in three provinces, namely Aceh (13.3%) followed by Bengkulu (10.5%), and Bali (8.5%). The purpose of this study was to determine the relationship of ergonomic knowledge to complaints of MSDs in PT field workers. PP construction project Bali International Hospital Sanur. The type of research used is observational analytic with a cross-sectional design. The population of this study was PT. PP construction project Bali International Hospital Sanur. Sampling by stratified random sampling method. The research instrument used is a questionnaire. Data analysis was carried out univariate and bivariate (Chi-Square alternative test was used). The results showed that there was a significant relationship between ergonomic knowledge and complaints of Musculoskeletal Disorders (MSDs) in PT. Bali International Hospital Sanur construction project PP (p=0.018). The company is expected to routinely provide training related to work ergonomics to workers so as to reduce MSDs complaints arising from work. Keywords: Musculoskeletal Disorders (MSDs), Construction Workers, Knowledge of Ergonomics